2014
DOI: 10.3390/diseases2030226
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Acyclic Retinoid in the Chemoprevention of Hepatocellular Carcinoma: Therapeutic Strategy Targeting Phosphorylated Retinoid X Receptor-α

Abstract: Hepatocellular carcinoma (HCC) is an aggressive disease with poor prognosis due to its high rate of recurrence after the initial curative treatment. Therefore, development of effective therapeutic strategies that can prevent recurrence and secondary tumor formation is required to improve the clinical outcomes of HCC patients. Malfunctioning of the retinoid X receptors (RXRs) of HCC patient by activation of the Ras-mitogen-activated protein kinase (MAPK) signaling pathway is strongly associated with hepatocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
(164 reference statements)
1
1
0
Order By: Relevance
“…It releases cytochrome c, which activates caspase-9 then cleaves caspases-3, -6, and -7, thereby affecting morphological and biochemical features of apoptosis with the intrinsic pathway of late apoptosis, including chromatin condensation, chromatin margination, and nuclear fragmentation. These characteristics of late apoptosis were found in C6-GSCs treated with 9-cis RA in this study [ 6 , 14 , 34 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It releases cytochrome c, which activates caspase-9 then cleaves caspases-3, -6, and -7, thereby affecting morphological and biochemical features of apoptosis with the intrinsic pathway of late apoptosis, including chromatin condensation, chromatin margination, and nuclear fragmentation. These characteristics of late apoptosis were found in C6-GSCs treated with 9-cis RA in this study [ 6 , 14 , 34 ].…”
Section: Discussionsupporting
confidence: 62%
“…The present study showed that combination of 9-cis RA with Met induced a higher percentage of late apoptosis in C6-GSCs than single treatment with 9-cis RA or Met. Met affected the morphology of early apoptosis whereas 9-cis RA bound to RARs, RXRs, and caused DNA fragmentation [ 10 , 21 , 34 ]. Moreover, the mechanism of apoptosis, confirmed by western blot, shows cleaved caspase-3 in Met-, 9-cis +RA- and Met+ 9-cis RA-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%